The brand personality dimensions of business-to-business firms: a content analysis of employer reviews on social media. Issue 2 (3rd April 2019) - Robertson, Jeandri; Lord Ferguson, Sarah; Eriksson, Theresa; Näppä, Anna
ABSTRACT: Purpose : The purpose of this paper is to explore the brand personalities that employees are creating of their employer brands, in particular business-to-business (B-to-B) brands, when describing these brands on social media. We examine how the brand personalities, based on written online reviews, differ between high- and low-ranked, and high- and low-rated brands. Methodology/Approach : 6, 300 written employee reviews from a social media platform, Glassdoor, are used for content analysis in DICTION, to determine the brand personality dimensions they communicate (J. L). An independent B-to-B brand ranking data source, Brandwatch, is used as a reference to various brands' level of ranking, while an ANOVA test is used to determine whether there is a difference in the brand personality trait means when comparing high and low-ranked, and high- and low-rated brands. Findings : Our findings suggest that a strong social media presence does not equate to a strong employer brand personality perception among employees, since there are no significant differences between B-to-B firms based on their rankings. Research Implications : Extant literature has mostly explored the impact of either critical reviews or favourable customer ratings and reviews on company performance, with very little research focusing on the B-to-B context. In addition, research employing DICTION for the purposes of content analysis of reviews is sparse. The methodology used in this study could thus be employed to further compare and contrast the reviews from a single company, dividing top and low starred reviews to compare discrepancies. Practical Implications : The results of this study show how online shared employee experiences of employer brands contribute to the formation of a distinct employer brand personality. From a managerial viewpoint, engaging with current and past employees and being cognizant of the online narratives that they share on social media, may be an early indicator of where the firm is lacking (or showing strength) in its' employee engagement. This would offer a way for firms to both understand their employer brand personality as well as gauge how they compare to top employers in a specific sector or industry. Originality/Value/Contribution : The study attempts to grow the literature of employee brand engagement in a B-to-B context, by recognizing the important role that employees play in engaging with their employer brand online. Two main contributions are offered. The first contribution relates to the finding that employees perceive highly-rated B-to-B brands as being more competent, exciting, sincere and sophisticated than low-rated B-to-B brands. Second, the methodology used in this study proves to be a novel and accurate way of comparing employee reviews and perceived employer brand personality, with the employer-created intended brand image.